Case Study on TGV Cinemas SDN BHD - Nur Dini Izzati Bt Sapian; Daisy Mui Hung Kee; Nurul Nadia Bt Abu Hassan; Nur Farah Izzah Bt Ahmad Faizh; Nadia Izzati Bt Miswan (AIBPM Publisher, 2019)
The project is about a case study on TGV Cinemas Sdn Bhd. TGV Cinemas is one of Malaysia’s premier film exhibition companies and established its name as a pioneer of cinema industry. We focus on the issues faced by this company which are inefficiency of customer services such as call centre and online movie ticket purchase, employees’ services, unreasonable food and beverages prices and maintenance of hall. The methodology that we employed to conduct this project is by interviewing the employees, distributing questionnaire among random people and online research. This study will discuss the solutions that can be implemented by the company to solve these problems which are improving their website system, expand employees’ skills, adjust their prices for foods and beverages and perform regular inspection. Keywords: TGV, Cinema Industry, Customer Services, Employees’ Services, Unreasonable Food and Beverages Prices, Maintenance of Hall